Efektivitas Alat Pengutip Buah Kelapa Sawit Modifikasi pada Masa Tanaman Menghasilkan - . Yulianto; Aang Kuvaini; Ata Olga Yogantara (Politeknik Kelapa Sawit Citra Widya Edukasi, 2021)
This research discusses the effectiveness of the modified palm oil loose fruit collecting tool at the productive plant. This research was conducted in community oil palm plantations in Desa Lubuk Bento Village, Kecamatan Pondok Suguh, Kabupaten Mukomuko, Provinsi Bengkulu, from 2020, 26th May to 2020, 30th July. The research purpose was to obtain alternative palm oil loose fruit collecting tool at the productive plant, as well as to determine the effect the use of modified palm oil loose fruit collecting tool to the effectiveness and efficiency of palm oil loose fruit collecting activities. The research method used is a functional design in terms of function or usefulness of the modified collecting tool. This research consist of two stages, ie: 1) literature study and tool design; and 2) the process of assembling and testing the tool. The parameters observed were the palm oil loose fruit collecting time, as well as the number and quality of palm oil loose fruit collected. The result showed that the use of modified palm oil loose fruit collecting tool could increase work performance from 0.21 WD/ha to 0.13 WD/ha.